Acylative kinetic resolution of racemic heterocyclic amines with (R)-2-phenoxypropionyl chloride. Issue 24 (31st December 2016) - Vakarov, Sergey A.; Gruzdev, Dmitry A.; Chulakov, Evgeny N.; Sadretdinova, Liliya Sh.; Tumashov, Andrey A.; Pervova, Marina G.; Ezhikova, Marina A.; Kodess, Mikhail I.; Levit, Galina L.; Krasnov, Victor P.; Charushin, Valery N.
Graphical abstract: Abstract: The acylative kinetic resolution of racemic heterocyclic amines such as 3, 4-dihydro-3-methyl-2 H -[1, 4]benzoxazines, 3, 4-dihydro-3-methyl-2 H -[1, 4]benzothiazine, 2-methyl-1, 2, 3, 4-tetrahydro-quinolines and 2-methylindoline with enantiopure ( R )-2-phenoxypropionyl chloride has been studied. It has been found that acylation of 3, 4-dihydro-3-methyl-2 H -[1, 4]benzothiazine proceeds with the best stereoselectively when compared with other racemic amines. An efficient method for the preparation of ( S )-3, 4-dihydro-3-methyl-2 H -[1, 4]benzothiazine (99.4% ee ) via a kinetic resolution protocol was developed. The possibility of recycling ( R )-2-phenoxypropionic acid has been demonstrated. Abstract : ( R )-2-Phenoxypropionic acid: C9 H10 O3 [ α ]D 20  = +21.1 ( c 1.0, CHCl3 ) Source of chirality: Ethyll -lactate Absolute configuration: (2 R ) Abstract : (3 S )-7, 8-Difluoro-3, 4-dihydro-3-methyl- N -[(2′ R )-2′-phenoxypropionyl)]-2 H -[1, 4]benzoxazine: C18 H17 F2 NO3 [ α ]D 20  = +63.5 ( c 1.0, CHCl3 ) Source of chirality: Ethyll -lactate Absolute configuration: (3 S, 2′ R ) Abstract : (3 S )-3, 4-Dihydro-3-methyl- N -[(2′ R )-2′-phenoxypropionyl)]-2 H -[1, 4]benzoxazine: C18 H19 NO3 [ α ]D 20  = +117 ( c 1.0, CHCl3 ) Source of chirality: Ethyll -lactate Absolute configuration: (3 S, 2′ R ) Abstract : (3 S )-3, 4-Dihydro-3-methyl- N -[(2′ R )-2′-phenoxypropionyl)]-2 H -[1, 4]benzothiazine: C18 H19 NO2 S [ α ]D 20  = +198 ( c 1.3, CHCl3 ) Source of chirality: Ethyll -lactate Absolute configuration: (3 S, 2′ R ) Abstract : (2 S )-2-Methyl- N -[(2′ R )-(2′-phenoxypropionyl)]-1, 2, 3, 4-tetrahydroquinoline: C19 H21 NO2 [ α ]D 20  = +192 ( c 0.4, CHCl3 ) Source of chirality: Ethyll -lactate Absolute configuration: (2 S, 2′ R ) Abstract : (2 S )-6-Fluoro-2-methyl- N -[(2′ R )-(2′-phenoxypropionyl)]-1, 2, 3, 4-tetrahydroquinoline: C19 H20 FNO2 [ α ]D 20  = +214 ( c 1.0, CHCl3 ) Source of chirality: Ethyll -lactate Absolute configuration: (2 S, 2′ R ) Abstract : (2 S )-2-Methyl- N -[(2′ R )-(2′-phenoxypropionyl)]-indoline: C18 H19 NO2 [ α ]D 20  = +43.7 ( c 0.6, CHCl3 ) Source of chirality: Ethyll -lactate Absolute configuration: (2 S, 2′ R ) Abstract : (2 R )-2-Methyl- N -[(2′ R )-(2′-phenoxypropionyl)]-indoline: C18 H19 NO2 [ α ]D 20  = +1.3 ( c 0.8, CHCl3 ) Source of chirality: Ethyll -lactate Absolute configuration: (2 R, 2′ R )